‘¿Para qué un museo?’: A reflection from Latin America upon the fragility and necessity of museums - Burón, Manuel (2024)
we want to emphasise in this article that the perishable nature of collections remains a characteristic of them even today. To think about the museum in terms of its perishable nature, the article presents two Latin American examples. Far from presenting the history and complexity of Latin American museums, this article is a plea for a concept of the museum that acknowledges the idea of impermanence and perishability. For that purpose, we analyse historical circumstances in which the actors asked themselves why this or that museum had been created. We refer to provincial natural history museums in nineteenth-century Argentina and community collections in contemporary Mexico: two different contexts that reflect the importance of the fields of natural history and of anthropology in those countries. These two sections exemplify two historical trends. In the first, museums are understood as places to produce knowledge, linked to the materials needed for a scientific discipline and organised around the objects stored, but not always displayed, in its buildings. The collections analysed in this section as well as in the second, reveal that collecting occurred beyond the metropolis and involved professionals and vocational scientists self-organised around common interests and working in network. The second refers to the late twentieth-century trope on the importance of community museums, namely the need to keep things where they belong. What happens when this is imposed over a community that does not care about museums? Why a museum at all?International trends and temporalities characterise the history of worldwide museums, including those established in the Americas, where historiography has showed the existence of different museum ‘waves’, such as those museums created in the 1820s just after independence: Buenos Aires (1812–1823), Rio de Janeiro (1818), Santiago de Chile (1822), Bogotá en Colombia (1823), Ciudad de México (1825), Lima (1826) and Montevideo (1837).3 In those years, museums emerged everywhere with a port that connected cities to the world, bringing and exporting objects, news and novelties. From Whitby in the UK to Charleston in North Carolina, the 1820s witnessed the establishment of untold numbers of museums, showing that what happened in Ibero-America was part of an international trend that perceived museums as something needed for being fashionable. Miruna Achim has characterised the period that started in the 1820s in the Americas as the ‘trial years’, meaning that museums—sometimes linked to a learned society that promoted the gathering and exchange of data and objects—had fragile existences, menaced by political turmoil and permanent financial crises.4 Later some of those museums were re-founded, reoriented and renamed. Institutional historiographies have treated them as if they had remained the same all through their history, a problem anchored in the idea of permanence that veils the transformations and losses that marked their survival.